Pelayanan Informasi Pendidikan Tinggi melalui Sosialisasi Penerimaan Mahasiswa Baru - Arianto, Arianto; Novyanti, Fitri; Rohmah, Siti; Fatriana, Disya (-, 2026)
Limited access and understanding of higher education information for high school students is a major obstacle in planning further study, especially in non-urban areas. This condition is also experienced by students of Wahid Hasim Tersono High School, Batang Regency, who still have limited knowledge regarding new student admissions, study program options, and higher education financing and scholarships. Therefore, this community service activity was carried out with the aim of providing higher education information services through targeted and educational new student admissions socialization. The service method used was a participatory-educational approach with stages of preparation, implementation, and evaluation. The activity was carried out through interactive lectures, discussions, questions and answers, and educational consultation services. Success was measured using a Likert scale questionnaire, student participatory observation, and limited reflection with the school. The results of the activity showed an increase in student understanding and attitudes towards higher education. As many as 81% of students understood the new student admissions pathway, 78% showed increased motivation to continue their education to higher education, and 74% gained new understanding regarding financing and scholarships. This activity also encouraged changes in student mindsets and strengthened the school's role in supporting further education.